Legal Consequences of Events of Default in Sales and Purchase Agreements - Nathanael, Enrique; Djajaputra, Gunawan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research discusses the legal consequences of default in a sale and purchase agreement. Using a normative approach, this research analyzes the legal regulations governing the issue of default in sales and purchase agreements. The research results concluded that default resulted in a violation of agreed obligations, which could result in a lawsuit for breach of contract or an unlawful act. Dispute resolution can be done through negotiation, mediation or arbitration. Negotiation, both of interests and rights, is an important process in forming contracts, with the aim of reaching an agreement that is profitable for all parties. In conclusion, success in business and dispute resolution often depends on the ability to negotiate well and adhere to promises that have been made.